Saevitia in the massacres of the colombian war (2008)
Starting from a description of the massacres in the region of Urabá between 1988 and 2002, this text formulates as a hypothesis that the appearance of saevitia (excessive cruelty) depends on factors such as war space/time, representations of the enemy, military asymmetry and insufficient use of political approaches. According to the author, the characteristics of saevitia in the massacres during the recent decades in the Colombian conflict contrasts with the period known as The Violence (1946-1965), which not only reflects a change in the phenomenology of terror but in the nature of contemporary political violence.